Sacrificing Paradise: Indonesia’s Green Energy Ambitions and the Future of Raja Ampat - Maspul, Kurniawan Arif (Indonesian Journal Publisher, 2025)
Raja Ampat, Indonesia’s ecological crown jewel, stands on the brink of ruin. Revered as the Amazon of the seas, this marine sanctuary harbors 75% of the world’s coral species and anchors the Coral Triangle’s climate resilience. Yet, a 2025 illegal nickel mining scandal exposed a harrowing paradox: the global rush for green energy minerals is devastating the ecosystems that sustain life. Enabled by weak governance, regulatory capture, and greenwashing, extractive industries have violated protected waters and Indigenous rights, threatening both biodiversity and cultural heritage. This study explores the environmental, geopolitical, and social fallout of Raja Ampat’s exploitation, revealing how the Global North’s decarbonization agenda externalizes ecological harm to the Global South. It argues that safeguarding Raja Ampat is not just a national duty but a global moral imperative. True sustainability demands centering Indigenous sovereignty, reforming environmental governance, and building ethical, transparent supply chains. Raja Ampat’s fate is a decisive moment for planetary stewardship — a test of whether humanity will prioritize ecological integrity over extractive greed.